Do The CSR Mission And Emissions Disclosure Characterize The Company’s Success? - Muhammad Jafar Shodiq (Universitas Trisakti, 2017)
In the current global warming situation, disclosure of emissions in annual reports is a necessity. Legitimacy from the public is a strategic key to future success. The bottom line of disclosing emissions in annual reports is global sustainability. However, there are doubts about the correlation between disclosure of emissions and future success. If the company does not have a CSR mission, the disclosure of emissions is only of short-term interest and is not correlated with global sustainability. This study reveals the characteristics of successful and non-successful companies associated with the CSR mission and disclosure of carbon emissions in the annual report. By using a sample of 114 manufacturing companies listed on the Indonesia Stock Exchange, this study shows that successful companies are characterized by having a strong CSR mission and commitment to disclosing emissions.